Citrus tristeza virus p23: a unique protein mediating key virus–host interactions - Flores, Ricardo; Ruiz-Ruiz, Susana; Soler, Nuria (Frontiers in Microbiology, 2013)
The large RNA genome of CTV (ca. 20 kb) contains 12 open reading frames (ORFs), with the 3’-terminal one corresponding to a protein of 209 amino acids (p23) that is expressed from an abundant subgenomic RNA. p23, an RNA-binding protein with a putative Zn-finger domain and some basic motifs, is unique to CTV because no homologues have been found in other closteroviruses, including the type species of the genus Beet yellows virus (despite both viruses having many homologous genes). Consequently, p23 might have evolved for the specific interaction of CTV with its citrus hosts. From a functional perspective p23 has been involved in many roles: i) regulation of the asymmetrical accumulation of CTV RNA strands, ii) induction of the seedling yellows syndrome in sour orange and grapefruit, iii) intracellular suppression of RNA silencing, iv) elicitation of CTV-like symptoms when expressed ectopically as a transgene in several Citrus spp., and v) enhancement of systemic infection (and virus accumulation) in sour orange and CTV release from the phloem in p23-expressing transgenic sweet and sour orange. Moreover, transformation of Mexican lime with intron-hairpin constructs designed for the co-inactivation of p23 and the two other CTV silencing suppressors results in complete resistance against the homologous virus. From a cellular point of view, recent data indicate that p23 accumulates preferentially in the nucleolus, being the first closterovirus protein with such a subcellular localization, as well as in plasmodesmata. These major accumulation sites most likely determine some of the functional roles of p23.